Integration Of AI In Leadership Decision-Making To Improve Efficiency And Accuracy Method: Literature Review - Nabilla, Sabbatun; Aspuri, Anggun Sesqi; Aini, Dia Nur; Anshori, Mochammad Isa (LPPJPHKI Universitas Dehasen Bengkulu, 2025)
This research analyzes the role of artificial intelligence (AI) in leadership decision-making to improve efficiency and accuracy. Using the literature review method, the research identified that AI is capable of processing big data quickly, providing in-depth analysis, and minimizing human error, thus supporting leaders in making more informed and data-driven decisions. However, AI integration also poses ethical challenges, such as algorithm bias and lack of transparency, which require critical consideration. This research emphasizes the importance of striking a balance between AI utilization and leaders' emotional intelligence to ensure that decisions are not only efficient and accurate, but also ethical and oriented towards organizational well-being. In addition, improving leaders' digital competencies is key in optimizing the use of AI. The results contribute to the development of an adaptive and inclusive technology-based leadership model, as well as recommendations for future in-depth research related to the impact of AI on organizational dynamics and ethical regulation.